Inverse effects of supporting electrolytes on the electrocatalytic nitrate reduction activities in a Pt|Nafion|Pt–Cu-type reactor assembly. Issue 14 (28th January 2016) - Hasnat, Mohammad A.; Safwan, Jamil A.; Rashed, M. A.; Rahman, Zidnia; Rahman, Mohammed M.; Nagao, Yuki; Asiri, Abdullah M.
Abstract : A Pt|Nafion|Pt–Cu assembly can exhibit its best reduction reaction efficiency in the absence of any supporting electrolytes. Adsorption of supporting electrolytes decreases efficiency by registering an increase of charge transfer resistance. Abstract : In this article, the effects of Cl − and SO4 2− ions on the electrocatalytic nitrate reduction activities in a sandwich-type reactor assembly are illustrated. It was noticed that a Pt|Nafion|Pt–Cu assembly offers its best efficiency in the absence of any supporting electrolytes. The Pt–Cu thin layers adsorb chloride and sulphate ions firmly, and this adsorption blocks the H + reducing sites at the cathode end of the catalytic assembly, leading to a decrease in catalytic efficiency. In the presence of chloride and sulphate ions, the reduction reactions of NO3 − and NO2 −, respectively, are relatively favoured.